Motor neuron synapse and axon defects in a C. elegans alpha-tubulin mutant. - Renee Baran (Public Library of Science (PLoS), 2010)
Regulation of microtubule dynamics underlies many fundamental cellular mechanisms including cell division, cell motility, and transport. In neurons, microtubules play key roles in cell migration, axon outgrowth, control of axon and synapse growth, and the regulated transport of vesicles and structural components of synapses. Loss of synapse and axon integrity and disruption of axon transport characterize many neurodegenerative diseases. Recently, mutations that specifically alter the assembly or stability of microtubules have been found to directly cause neurodevelopmental defects or neurodegeneration in vertebrates. We report here the characterization of a missense mutation in the C-terminal domain of C. elegans alpha-tubulin, tba-1(ju89), that disrupts motor neuron synapse and axon development. Mutant ju89 animals exhibit reduction in the number and size of neuromuscular synapses, altered locomotion, and defects in axon extension. Although null mutations of tba-1 show a nearly wild-type pattern, similar axon outgrowth defects were observed in animals lacking the beta-tubulin TBB-2. Genetic analysis reveals that tba-1(ju89) affects synapse development independent of its role in axon outgrowth. tba-1(ju89) is an altered function allele that most likely perturbs interactions between TBA-1 and specific microtubule-associated proteins that control microtubule dynamics and transport of components needed for synapse and axon growth.